My story : justice in the wilderness - Thomas, Tommy, 1952-; Strategic Info Research Development (Petaling Jaya, Selangor : Strategic Information and Research Development Centre, 2021)
'As the first private practitioner in some 70 years to be appointed Attorney General of Malaysia, Tommy Thomas describes his experience in the highest legal office in the land in this highly personal book.The former AG discusses key decisions he made, including the prosecution of former Prime Minister Najib Razak, Jho Low, Arul Kanda and Goldman Sachs for their roles in the 1mdb scandal. His book is the first insider's account by a senior Pakatan Harapan government official on the achievements, disappointments and failures of the first non-Barisan administration in the 60-year history of independent Malaysia. His authentic voice is captured in this candid memoir, and is recommended reading for anyone interested in Malaysian politics and the law.'--Page 4 of cover.
Includes bibliographical references and index.
Keywords: Thomas, Tommy, -- 1952-; Attorneys general -- Malaysia -- Biography; Lawyers -- Malaysia -- Biography; Malaysia -- Politics and government